1989
DOI: 10.3177/jnsv.35.291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cholesterol feeding on the distribution, metabolism, and accumulation of pentachlorobenzene in rats.

Abstract: SummaryTo investigate the influence of cholesterol content in tissue on the distribution, metabolism, and accumulation of pentachlorobenzene (PECB), rats were fed on a cholesterol-enriched (CHE) diet or a basal diet for 4 weeks. At two weeks, a single dose or a 6-day dosage of PECB was orally administered. The serum cholesterol concentration in the CHE diet group was 2.1-2.9 times higher than that in the basal diet group, while the serum triglyceride concentration decreased. The serum lipid levels were similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…The decrease in fat tissue mass reduces its capacity to store PECB there, increases PECB concentrations in the blood and liver, and thus accelerates PECB metabolism by the hepatic drug-metabolizing enzymes. This is supported by the facts that blood concentrations of PECB on days 1-2 and PCP on days 1-4 in the restricted diet groups were significantly higher than those in the AD group (Tables 3 and 5), and that the biological half-life of PECB in rats was approximately one day (18). These phenomena were quite similar to those observed in an experiment using young and adult rats (9).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The decrease in fat tissue mass reduces its capacity to store PECB there, increases PECB concentrations in the blood and liver, and thus accelerates PECB metabolism by the hepatic drug-metabolizing enzymes. This is supported by the facts that blood concentrations of PECB on days 1-2 and PCP on days 1-4 in the restricted diet groups were significantly higher than those in the AD group (Tables 3 and 5), and that the biological half-life of PECB in rats was approximately one day (18). These phenomena were quite similar to those observed in an experiment using young and adult rats (9).…”
Section: Discussionsupporting
confidence: 79%
“…PECB accumulated in fat tissue because of its lipophilic properties, whereas PCP could not be detected in fat tissues (18). Therefore, the transformation of PECB to PCP by cytochrome P®450 seems to be an important step in the excretion of PECB accumulated in the body.…”
Section: Discussionmentioning
confidence: 98%
“…As the concentration of hepatic fats, especially triglycerides, was high in the lard group (Table 2), the degree of interac tion of HCB with the hepatic drug-metabolizing enzymes might have been reduced, resulting in the impaired metabolism of HCB. We have observed similar findings using PECB (22,33). These findings in the lard group suggest that both the decrease in fat tissue mass and the interaction of HCB with hepatic drug-metabolizing enzymes were responsible for the increase of HCB metabolism in the fish oil group.…”
Section: Discussionsupporting
confidence: 76%
“…A previous study indicated the involvement of cytochrome P-450 3A in the microsomal oxidation of HCB to pentachlorophenol (PCP) and to tetrachlorobenzoquinone (TCBQ) (Van Ommen et al, 1989). PECB is also relatively rapidly metabolized and is oxidized to the same products as in the metabolism of HCB, that is, PCP and TCBQ (Besten et al, 1989;Umegaki and Ichikawa, 1989). Both compounds have been reported to be hepatotoxic and immunotoxic and to affect thyroid hormone homeostasis (Carlson and Tardiff, 1976;Vos et al, 1979;Besten et al, 1993).…”
Section: Introductionmentioning
confidence: 99%